Land tenure, conservation and development in Southeast Asia - Eaton, Peter (RoutledgeCurzon contemporary Southeast Asia series, 2004)
This book examines the relationship between land tenure, conservation and rural development in the context of the Southeast Asian archipelago and is particularly concerned with people living in and around national parks and other protected areas.